Utility of gastric biopsy in diagnosing IgG4‐related gastrointestinal disease. Issue 2 (30th December 2020) - Uchino, Kaori; Notohara, Kenji; Uehara, Takeshi; Kuraishi, Yasuhiro; Itakura, Junya; Matsukawa, Akihiro
Abstract : The utility of gastric biopsy for diagnosing immunoglobulin (Ig)G4‐related gastrointestinal disease (IgG4‐GID) remains unclear. Bottom‐heavy plasmacytosis (BHP) is a distinct feature of IgG4‐GID. To clarify the feasibility of using gastric biopsies to diagnose BHP in IgG4‐GID, we analyzed the histological features and immunostaining of gastric biopsy specimens from 31 known IgG4‐related disease (IgG4‐RD) patients and we assessed the presence of BHP in 1696 consecutive routine gastric biopsies. Cases with both >10 IgG4‐positive plasma cells per high‐power field and an IgG4/IgG‐positive ratio >40% were defined as IgG4‐high. Ten of the 31 IgG4‐RD patients were concluded to have IgG4‐GID, in which IgG4‐positive plasma cells were notably detected at the deeper part of the mucosa. Six cases displayed BHP whereas the remaining four cases showed transmural infiltration with concomitant Helicobacter pylori ‐associated gastritis. In addition to BHP, we identified two unique histologic features for IgG4‐GID: plasmacytic aggregation in the muscularis mucosae and permeative plasmacytic infiltration between fundic glands in the non‐atrophic mucosa. Six of the routine cases (0.35%) displayed BHP, including a case with IgG4‐RD. IgG4‐GID can be suspected by the presence of gastric biopsy specimens with characteristic histological features. Such cases are recommended to undergo further examinations to determine whether IgG4‐RD is present.